(untitled) (Revista Electrónica REDINE, 2018)
The research had as purpose analyze the effectively of the Preparaduría Academica’s Program on the basis of the teachers’ opinion supervisors, preparers and students benefited in the Program of Pre.School education and integral Education of Barquisimeto’s Pedagogic Institute. It place in a field research of descriptive character of opinion type. The population was constituted by a whole of one thousand three hundred sixty five (1365) students, six (06) teachers supervisors of students preparers and six (06) students preparesrs. The sample remained constituted by 78 pupils. For the compilation of the information, trhee questionnaires were designed of questions close with different categories of answers. The obtained information, it was tabulated across the statistical package SPSS 11. The results allowed to colclude that Preparaduria’s Program shows a trend in average fall as for his effectively.